Univariate and multivariate models for the prediction of life-threatening complications in 586 cases of deep neck space infections: retrospective multi-institutional study. Issue 9 (5th June 2017) - Mejzlik, J; Celakovsky, P; Tucek, L; Kotulek, M; Vrbacky, A; Matousek, P; Stanikova, L; Hoskova, T; Pazs, A; Mittu, P; Chrobok, V
Abstract: Objective: To identify deep neck infection factors related to life-threatening complications. Methods: This retrospective multi-institutional study comprised 586 patients treated for deep neck infections between 2002 and 2012. The statistical significance of variables associated with life-threatening complications of deep neck infections was assessed. Results: During treatment, life-threatening complications occurred in 60 out of 586 cases. On univariate analysis, life-threatening complications were linked to: dyspnoea, neck movement disturbance and dysphonia (all p < 0.001); and parapharyngeal, anterior visceral or pretracheal deep neck involvement (all p < 0.002). Aetiology was significantly linked to tonsils ( p < 0.001). Regarding infection type, fasciitis was a significant factor ( p < 0.001). Candida albicans was a significant bacterial culture ( p < 0.001). A multivariate step-wise model disclosed fewer significant variables: retropharyngeal space ( p = 0.005) and major blood vessels area ( p = 0.006) involvement, and bacterial culture C albicans ( p < 0.001). Conclusion: It can be predicted that patients with deep neck infections, with neck movement disturbances, dysphonia, dyspnoea and swelling of the external neck, accompanied by severe pain, and inflammatory changes in the retropharyngeal space and large vessel areas, with culture-confirmed infection of C albicans, are likely to develop life-threatening complications.